BUILDING CUSTOMER LOYALTY THROUGH SERVICE QUALITY AND CUSTOMER SATISFACTION: AN EMPIRICAL STUDY AT PT IPC TPK TANJUNG PRIOK - Alfi Kamil Rafi; Zahroni, Zahroni; Lira Agusinta; Edhie Budi Setiawan; Sandriana Marina (LPSDI Bina Patria, 2025)
This study examines the effect of service quality—comprising the dimensions of resources, outcomes, processes, management, and image—on customer loyalty at PT IPC TPK Tanjung Priok, with customer satisfaction as a mediating variable. The research is motivated by suboptimal service delivery, weak regulations, limited satisfaction surveys, and inconsistent prior findings. A descriptive–causal quantitative design was applied to 107 purposively selected port service users, who completed a structured questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that all five service quality dimensions jointly and significantly shape perceived service quality (significant of outer loading, non-multicollinearity, and strong redundancy result). Furthermore, service quality has a very strong positive effect on customer satisfaction, and customer satisfaction fully mediates the relationship between service quality and customer loyalty in this research. These findings affirm that enhancing loyalty can be achieved only through the improvement of satisfaction. Practically, port management should upgrade facilities and staff competencies, optimize operational processes, strengthen management practices, and build institutional image to foster long-term satisfaction and loyalty.